Levels of Fine Particle Concentrations in Schools and Postexercise Pulmonary Function Disorders in Schoolchildren in Brazzaville - Nsompi, Florent; Mabounda Kounga, Paul Roger; MOUSSOUAMI, Simplice Innocent; BOUSSANA, Alain; Bouhika, Eddie Janvier; Messan, Folly (My University, 2023)
Context: Fine particles (PM2.5 and PM10) can accumulate in classrooms and in schoolyards located near urban roads. PM2.5 and PM10 can initiate, develop and exacerbate exercise-induced bronchospasm (EIB). This study aimed to assess the concentration levels of PM2.5 and PM10 in schools and to determine the rate of sensitivity to EIB among schoolchildren. Methods: A total of 128 students (67 girls and 61 boys) with an average age of 11 participated in this study. An ISAAC II questionnaire on respiratory symptoms was administered. PM2.5 and PM10 were measured. A 6-minute stress test was performed. Spirometry was performed. The ratio (I/O) of the concentrations of PM2.5 and PM10 recorded inside (I) the classrooms to those obtained outside (O) the classrooms was equal to 1 (I/O = 1). Results: The concentrations of PM2.5 and PM10 recorded inside the classrooms and those obtained outside the classrooms were higher than the values recommended by the WHO. 29 students out of 128 were diagnosed as sensitive to EIB [EIB (+)], i.e. , a rate of sensitivity to EIB of 22.66%. A drop in postexercise PEF of 17.396% was observed among EIB (+) students. Conclusion: Schoolchildren in schools located near highways are exposed to high levels of PM2.5 and PM10 concentrations. Exposure to PM2.5 and PM10 played an important role in the initiation and exacerbation of exercise-induced bronchospasm in schoolchildren from schools located near highways. Effective programs for improving air quality in schools must be put in place to reduce the effects of particulate pollution on the respiratory health of school children.
Keywords: Particulate Pollutants; Road Traffic; Exercise-Induced Bronchospasm; Schoolboy